PERUBAHAN FUNGSI LAHAN SAWAH DAN DAMPAKNYA TERHADAP KESEJAHTERAAN MASYARAKAT ACEH BESAR MENURUT TA?ARRUF F? ISTI’M?L AL-M?L - Ramadhan, Syahrul; Maulana, Muhammad; Amri, Khairul (JIM : Journal Of International Management, 2025)
This study examines changes in the function of rice fields and their impact on community welfare in Aceh Besar from the perspective of Tasarruf Fi Istimal Al-Mal. The conversion of rice fields into non-agricultural land has become a critical issue, as rice fields serve as a primary source of food security and farmers’ income. The study aims to identify the factors driving land-use change, analyze its economic and environmental impacts on farming communities, and assess the phenomenon through the lens of Islamic economic principles. A qualitative naturalistic approach was employed. Data were collected through in-depth interviews with affected communities and village officials, as well as participatory field observations. Data analysis was conducted inductively through data reduction, narrative presentation, and conclusion drawing based on fiqh muamalah perspectives. The finding is influenced by economic pressures, housing demands, and weak local land protection policies. The negative impacts include reduced agricultural land, declining farmers’ income and employment opportunities, and increasing social inequality. From the perspective of Tasarruf Fi Istimal Al-Mal, the study emphasizes the need for responsible and equitable asset management to ensure food security and long-term community welfare.